Luciferase Reporter Assay in Drosophila and Mammalian Tissue Culture Cells. Issue 1 (14th March 2014) - Yun, Chi; DasGupta, Ramanuj
Abstract: Luciferase reporter gene assays are one of the most common methods for monitoring gene activity. Because of their sensitivity, dynamic range, and lack of endogenous activity, luciferase assays have been particularly useful for functional genomics in cell‐based assays, such as RNAi screening. This unit describes delivery of two luciferase reporters with other nucleic acids (siRNA/dsRNA), measurement of the dual luciferase activities, and analysis of data generated. The systematic query of gene function (RNAi) combined with the advances in luminescent technology have made it possible to design powerful whole genome screens to address diverse and significant biological questions. Curr. Protoc. Mol. Biol . 6:7‐23. © 2014 by John Wiley & Sons, Inc.